Nitrate-Induced Improvements in Exercise Performance Is Coincident With Exuberant Changes in Metabolic Genes and the Metabolome in Zebrafish (Danio rerio) Skeletal Muscle. (7th June 2021) - Keller, Rosa; Beaver, Laura; Reardon, Patrick; Stevens, Jan; Hord, Norman
Abstract: Objectives: Dietary nitrate (NO3 − ) supplementation improves exercise performance by reducing the oxygen cost of exercise and enhancing skeletal muscle function. However, the mechanisms underlying the beneficial effects on exercise performance are not well understood and may be supported by changes in metabolism within the skeletal muscle. The purpose of this study was to elucidate nitrate-induced changes in skeletal muscle energy metabolism associated with improvements in exercise performance that may reflect enhanced metabolic flexibility. Methods: Fish were exposed to sodium nitrate (60.7 mg/L, 303.5 mg/L, and 606.9 mg/L), or control water, for 21 days and analyzed at intervals during a strenuous exercise test. Nitrate storage in muscle was measured using chemiluminescence. We utilized nuclear magnetic resonance spectroscopy (NMR), liquid-chromatography tandem mass spectrometry (LC-MS/MS) untargeted metabolomics and real-time quantitative polymerase chain reaction (RT-qPCR) to determine changes in muscle metabolism with nitrate and exercise. Results: Nitrate treatment significantly increased muscle nitrate concentrations, while muscle nitrate levels declined with increasing exercise duration, and nitrate treatment was associated with a decrease in the oxygen cost of exercise. In skeletal muscle, nitrate treatment upregulated expression of genes central to nutrient sensing ( mtor ), glucose ( hk2 ) and lipid metabolism ( acaca ), redox signaling ( nrf2a ) and muscle differentiation ( sox6 ). Nitrate treatment caused rested skeletal muscle to have significantly increased metabolites directly linked to energy production (phosphocreatine (PCr), creatine (Cr), adenosine nucleosides, purines, glycolytic, fatty acid and tricarboxylic acid cycle (TCA) intermediates) and a concomitant decrease in these metabolites after exercise, compared to rested-control fish. Conclusions: Our data suggest that nitrate exposure may improve exercise performance by changing the metabolic programming of muscle prior to exercise, thus increasing the availability of energy producing metabolites required for exercise such as ATP and phosphocreatine. Funding Sources: Celia Strickland and G. Kenneth Austin III Endowment and National Institutes of Health.